Experimental characterisation of nanoelectronic devices at cryogenic temperatures - Tarancón Cebrián, Miguel; Pérez-Bailón, Jorge; Sánchez Azqueta, Carlos (Jornada de Jóvenes Investigadores del I3A, 2022)
This work presents the experimental characterisation of the behaviour at different temperatures of integrated transistors in a commercial integrated circuit in CMOS technology. The temperature range of interest covers the usual operating range of these devices (from -40 ºC to +80 ºC) and also includes the characterisation at ultra-low temperatures up to the cryogenic regime at 4 K.